Giant Hepatic Hemangioma Presenting as Gastric Outlet Obstruction - Aydin, C; Akbulut, S; Kutluturk, K; Kahraman, A; Kayaalp, C; Yilmaz, S (2013)
Hemangioma, a most frequently encountered primary benign tumor of the liver, is generally determined incidentally during the course of radiologic tests for other reasons. Most lesions are less than 3 cm and a significant proportion of patients are asymptomatic, although the size and location of the lesion in some patients may be associated with the onset of symptoms. Pressure on the stomach and duodenum of giant hemagiomas developing in the left lobe of the liver, in particular, may result in the development of abdominal pain, nausea, vomiting, and feeling bloated, which are characteristic of a gastric outlet obstruction. A 42-year-old man presented with findings of gastric outlet obstruction and weight loss as a result of a giant hepatic hemangioma. C1 [Aydin, Cemalettin; Akbulut, Sami; Kutluturk, Koray; Kayaalp, Cuneyt; Yilmaz, Sezai] Inonu Univ, Fac Med, Liver Transplantat Inst, TR-44280 Malatya, Turkey. [Kahraman, Aysegul] Inonu Univ, Fac Med, Dept Radiol, TR-44280 Malatya, Turkey.